A Case of Tinea Incognito: A Misuses of Steroid - Diah Mira Indramaya; Abdul Karim; Zahruddin Ahmad (Faculty of Medicine, Universitas Airlangga, 2019)
Background: Tinea incognito (TI) is a dermatophytic infection which has lost its typical clinical appearance because of improper use of steroids. Topical steroids in Indonesia are often used without prescription. The misuses of steroids has led to the emergence of TI. Clinical diagnosis of TI is still a challenge even by dermatologists, thus lead to a delay treatment. Purpose: To report a case of TI in child. Case: A 10-year-old girl presented with itchy ill defined erythematous patches on the face. The patch had appeared since 2 months before. The patient had already got topical and systemic corticosteroid but there were no improvement. Physical examination showed multiple papules on ill defined scaly erythematous patches on facial region. Potassium hydroxide examination revealed arthroconidia and septate hyphae, while from culture isolation Microsporum gypseum were identified. Diagnosis of TI was successfully made and the patient was treated with griseofulvin two times 125 mg per day orally for four weeks. The patient showed good result. Discussion: TI lesions usually lose their classic annular appearance thus the disease is likely to be confused with other diseases. It is important for dermatologist to consider fungal infection as differential diagnosis of prolong erythematous scaly lesions unresponsive to steroids or calcineurin inhibitors, and encourage of laboratory tests for mycological evaluation. Conclusion: Discontinuance of steroid and adminisration antifungal therapy promoted lesions improvement clinically and mycologically. It is important to regulate the topical steroid distribution and to educate primary care doctors about superficial dermatophytosis to reduce the increasing case of TI.